Health care for children and adolescents in Poland - Hejda, Grażyna; Mazur, Artur; Dembiński, Łukasz; Peregud-Pogorzelski, Jarosław; Jackowska, Teresa; Walczak, Mieczysław; Szczepański, Tomasz (Pediatria Polska - Polish Journal of Paediatrics, 2020)
Despite the constant tendency of decreasing birth rate, children and adolescents comprise one fifth of the Polish population. Health care for children is free and it is organised similarly to the care for adult patients. In primary health care, children can be under the medical care of general practitioners, family doctors, or paediatricians. In secondary and tertiary care, medical services are provided by paediatricians or doctors with paediatric subspecialties. The number of paediatricians and nurses is not sufficient and still differs from the European average. Nonetheless, population health indicators (e.g. infant mortality rate) are constantly improving and, despite the strong influence of the anti-vaccine movements, 90% of children are vaccinated according to the schedule.